2022
DOI: 10.3389/feart.2022.925358
|View full text |Cite
|
Sign up to set email alerts
|

Performance of CMIP6 HighResMIP Simulations on West African Drought

Abstract: This study evaluated the performance of seven CMIP6 HighResMIP models in the simulations of drought over two sub-regions of West Africa: the Guinea coast and the Sahel during the historical period of 1985–2014, in terms of the potential evapotranspiration index (PET), climatic water availability (CWA), and standardized precipitation evapotranspiration index (SPEI) at three time scales (i.e., 1, 3, and 12 months). The Climate Research Unit (CRU) TS v4.03 datasets were used as the observation reference. The obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…By selecting three CMIP6 models, we have aimed to assess the role of ECS in the prediction of aridity by using low, medium and high ECSs. Various studies have evaluated CMIP6's performance in modelling precipitation and temperature on continental or regional scales (Ajibola et al, 2020; Fan et al, 2020; Ajibola et al, 2022; Dong & Dong, 2021), and it has been shown that multi‐model ensembles perform better overall than individual models (Vogel et al, 2020; Zhao et al, 2021). Therefore, we have calculated the multi‐model means of the GFDL‐ESM4, MRI‐ESM2‐0 and IPSL‐CM6A‐LR models and assessed the results based on the multi‐model mean results.…”
Section: Methodsmentioning
confidence: 99%
“…By selecting three CMIP6 models, we have aimed to assess the role of ECS in the prediction of aridity by using low, medium and high ECSs. Various studies have evaluated CMIP6's performance in modelling precipitation and temperature on continental or regional scales (Ajibola et al, 2020; Fan et al, 2020; Ajibola et al, 2022; Dong & Dong, 2021), and it has been shown that multi‐model ensembles perform better overall than individual models (Vogel et al, 2020; Zhao et al, 2021). Therefore, we have calculated the multi‐model means of the GFDL‐ESM4, MRI‐ESM2‐0 and IPSL‐CM6A‐LR models and assessed the results based on the multi‐model mean results.…”
Section: Methodsmentioning
confidence: 99%
“…Precise precipitation simulation in West Africa is crucial for understanding the region's climate variability and change vulnerability. Previous studies have highlighted the importance of accurate precipitation simulation in the region, particularly in light of its susceptibility to climate extremes such as droughts and oods (Sarr, 2017;Almazroui et al, 2020;Ajibola et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Earth System (iHESP) (Small et al 2014;Chang et al 2020). These HR GCMs improve the simulation of rainfall characteristics and its associated governing mechanisms compared to their low resolution (LR) counterparts in tropical climates such as southern China (Xin et al, 2021), Malaysia (Liang et al, 2021), Indonesia (Hariadi et al, 2022;Kurniadi et al, 2022), tropical South America (Monerie et al 2020) and West Africa (Ajibola et al 2020;Ajibola et al 2022, Nkrumah et al 2022. We also use the M19 subregional classification (Fig.…”
Section: Introductionmentioning
confidence: 99%